Knowledge-driven economic growth: The case of Sub-Saharan Africa - Stephen Oluwatobi; Isaiah Oluranti Olurinola; Philip Alege; Adeyemi A. Ogundipe (African Governance and Development Institute (AGDI), 2018)
The experience of South Korea, India, China and Singapore reveals that developing economies can fasttrack development, leapfrog the stages of development and catch up with advanced economies by putting knowledge capital as the driver of development. If the knowledge economy is therefore a n accelerant of development for both advanced and developing economies, it is possible for Sub- Saharan African (SSA) economies to also catch up with advanced economies. It was on this basis that this study assessed the knowledge capacity of SSA and the effect it has on its economic advancement. Give n the importance of the interrelatedness among the knowledge economy elements, this study, thus, examined how the interaction effect between the elements of the knowledge economy affects economic growth in 32 SSA countries, for which data were available, over the period of 17 years (1996-2012). Using the System Generalized Method of Moments (SGMM), the study found out that institutions and human capital in SSA mitigate the effect of innovation on economic growth in the region, thus, making it a lean knowledge economy.
Keywords: 330; Economic Growth; Human Capital; ICT; Innovation; Institutions; Knowledge Economy